Herbal Beverage Packaging Design Training (The Object of The Study: UKM Herbal Village, Genteng-Candirejo, Surabaya) - Widyasari; Solicitor, Aileena; Yani, Aditya Rahman (Nusantara Science and Technology Proceedings, 2020)
Genteng-Candirejo Herbal Village Surabaya, is a center for Small and Medium Enterprises (UKM) producing national class herbal drinks with a total of 12 Trade Businesses (UD) operating under the auspices of the Mandiri Gencar (Genteng-Candirejo) UKM. The problem that arises from the results of observations and interviews of researchers with UMKM activists in Genteng-Candirejo Herbal Village is that the product packaging is still very simple and has not been designed attractively. The majority of UMKMs in Genteng-Candirejo Herbal Village do not have the knowledge and understanding related to product packaging so that it makes it difficult for them to market their products to a larger market the packaging of the product that is not ideal also gives the impression that herbal drinks are outdated products, and cannot communicate the image of Kampung Jamu Genteng-Candirejo Surabaya well. The solution to this problem is by providing training and counseling to members of the Genteng-Candirejo Herbal Village UMKM regarding the design of herbal drink packaging. The methods used in this activity are, first, the presentation method to convey several things related to knowledge of herbal beverage packaging. Second, the demonstration method to show how to make herbal beverage product packaging for the UKM Kampung Herbal Genteng-Candirejo. Third, practical methods to train the Genteng-Candirejo Herbal Village UKM group in making herbal drink packaging designs